2020
DOI: 10.1177/1087054720923736
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Sex Differences in ADHD Symptoms and Associated Cognitive Deficits

Abstract: Objective: A meta-analysis was carried out to determine whether there are sex differences among children and adolescents with ADHD on the primary symptoms of ADHD and on executive and attentional functioning. Method: Studies published from 1997 to 2017 comparing boys and girls with a valid ADHD diagnosis were retained. Results: The meta-analysis found boys with ADHD to be more hyperactive than girls with ADHD and boys to have more difficulties in terms of motor response inhibition and cognitive flexibility. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 103 publications
6
47
1
Order By: Relevance
“…Neurodevelopmental disorders are more common in boys than in girls, 12 but it is also known that neurodevelopmental problems have a less salient pattern in girls than in boys, and so can go undetected for a longer time. 30 A previous study of adolescents seeking MBS found more boys than girls with ADHD, 11 that is more in line with findings from population samples.…”
Section: Discussionsupporting
confidence: 80%
“…Neurodevelopmental disorders are more common in boys than in girls, 12 but it is also known that neurodevelopmental problems have a less salient pattern in girls than in boys, and so can go undetected for a longer time. 30 A previous study of adolescents seeking MBS found more boys than girls with ADHD, 11 that is more in line with findings from population samples.…”
Section: Discussionsupporting
confidence: 80%
“…It has also been suggested that sleep spindle abnormalities are an endophenotype of schizophrenia (51,54). Moreover, these disorders can be characterized with cognitive impairments as well (55)(56)(57). It has been demonstrated that sleep spindles and cognitive function are strongly associated (58,59), and as such, sleep spindle abnormalities might provide a key to interpreting cognitive malfunction (17).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not test for sex differences in the interactive effects of ADHD PGS and maltreatment given that our investigation was likely underpowered to do so. There are clear sex differences in the prevalence of ADHD (e.g., Carbonneau et al 45 ), and while Martin et al 46 recently showed no differences in mean ADHD PGS between males and female cases in the PGC, iPSYCH, as well as a registry-based Swedish sample, it remains unknown whether there may be sex-specific ADHD PGS x environment interactions for ADHD. Third, both ADHD symptoms and maltreatment were retrospectively reported when individuals were young adults.…”
Section: Discussionmentioning
confidence: 99%